Understanding of emotional abuse and sextortion among Ghanaian women on social media / Basiratu Lawal - Lawal, Basiratu (2022)
One of the greatest challenges in handling domestic abuse cases in Ghana is that abused women encounter opposition in reporting any form of abuse. In spite of these challenges, most women continue to report incidents of domestic violence to the newly created Women and Juvenile Unit (WAJU) of the Ghanaian police force in record numbers. The objective of this study is to identify the main causes of Emotional Abuse and Sextortion among Ghanaian Women and to understand how emotional abuse and sextortion affect Ghanaian women on social media. This study also explores how Ghanaian women overcome emotional abuse and sextortion on social media. The research work is developed to answer the following research questions: 1. How does emotional abuse and sextortion affect Ghanaian women on social media? 2. How does a Ghanaian woman overcome emotional abuse and sextortion on social media? 3. Why do Ghanaian Men use social media as tools of correction in marriage relationships in Ghana, as perceived by Ghanaian Women? 4. How can the criminal justice systems help to reduce emotional abuse and sextortion, as perceived by Ghanaian Women?. The theories used in this study are, Socialist Feminist standpoint theory and Goffman theory on family and gender equality. A qualitative method was used for identifying and characterising the in-depth interviews among 10 informants in Greater Accra, Ghana. The basic research design for this study was in-depth interviews and participant observation. A qualitative approach was adopted for the study and the method of interviews was constructed in an open-ended manner. The interviewer adopted the Excel software to perform data analysis. This software helps in data organization and management of large collections of qualitative data. The results of this study show that sextortion among Ghanaian women is caused by the fact that when the women question their husband's authority, they do not listen, come home late, and fail to show respect or cooperation and their comments are seen as nagging. From this analysis, it can be concluded that some Ghanaian men use sextortion as a tool to manipulate their intimate partners and to maintain their male superiority or dominance. The findings of this study show that some Ghanaian men perpetrate acts of emotional abuse and sextortion via social media because that is the easiest form of tool to extort their victims. It was discovered from the informants of this study that the perpetrators begin by building up virtual intimate relations with the women and when trust is built in the women, they start requesting sexual materials from the victim, after which sextortion starts. This is a typical example of what happened to informant E of this study. The perpetrator took her virginity, turned her into a sex machine and later exposed her nude pictures. With the prevalence of use of social media, especially among the local Ghanaian community, many Ghanaian women have fallen victim to many online illegal activities, such as sexting, nonconsensual Pornography, cyber dating abuse, and revenge pornography. When the abuse is perpetrated continuously, it leads to a state of emotional distress among the emotionally abused women, which is attributed to their sense of hopelessness.The findings show that sextortion related crimes are very difficult to prove because of the high level of confidentiality between the perpetrator and the victim. Evidence suggests that the way in which survivors or victims of sextortion try to overcome their problems are complex and vary from one victim to another. The data from this study also shows that sextortion and emotional abuse cases in Ghana are underreported.